Biogeography and diversification of colletid bees (Hymenoptera: Colletidae): emerging patterns from the southern end of the world - Eduardo A. B. Almeida; Marcio R. Pie; Seán G. Brady; Bryan N. Danforth (Journal of Biogeography, 2012)
Aim The evolutionary history of bees is presumed to extend back in time to the Early Cretaceous. Among all major clades of bees, Colletidae has been a prime example of an ancient group whose Gondwanan origin probably precedes the complete break‐up of Africa, Antarctica, Australia and South America, because modern lineages of this family occur primarily in southern continents. In this paper, we aim to study the temporal and spatial diversification of colletid bees to better understand the processes that have resulted in the present southern disjunctions. Location Southern continents. Methods We assembled a dataset comprising four nuclear genes of a broad sample of Colletidae. We used Bayesian inference analyses to estimate the phylogenetic tree topology and divergence times. Biogeographical relationships were investigated using event‐based analytical methods: a Bayesian approach to dispersal–vicariance analysis, a likelihood‐based dispersal–extinction–cladogenesis model and a Bayesian model. We also used lineage through time analyses to explore the tempo of radiations of Colletidae and their context in the biogeographical history of these bees. Results Initial diversification of Colletidae took place at the Late Cretaceous (≥ 70 Ma). Several (6–14) lineage exchanges between Australia and South America via Antarctica during the Late Cretaceous and Eocene epochs could explain the disjunctions observed between colletid lineages today. All biogeographical methods consistently indicated that there were multiple lineage exchanges between South America and Australia, and these approaches were valuable in exploring the degree of uncertainty inherent in the ancestral reconstructions. Biogeographical and dating results preclude an explanation of Scrapterinae in Africa as a result of vicariance, so one dispersal event is assumed to explain the disjunction in relation to Euryglossinae. The net diversification rate was found to be highest in the recent history of colletid evolution. Main conclusions The biogeography and macroevolutionary history of colletid bees can be explained by a combination of Cenozoic vicariance and palaeoclimatic changes during the Neogene. The austral connection and posterior break‐up of South America, Antarctica and Australia resulted in a pattern of disjunct sister lineages. Increased biome aridification coupled with floristic diversification in the southern continents during the Neogene may have contributed to the high rates of cladogenesis in these bees in the last 25–30 million years.